Fire without Smoke : Learning from the National Program on Improved Chulhas - Rehman, Ibrahim Hafeezur; Malhotra, Preeti (New Delhi: The Energy and Resources Institute and the World Bank, 2013)
A major section of over 720 million rural poor in India continue to depend on biomass sources for meeting their energy requirements. Most of these poor people continue to burn biomass in energy-inefficient devices, locally called Chulhas. This study report is based on an evaluation of the National Program for Improved Chulhas (NPIC) conducted as part of a larger Bank study entitled India : household energy, indoor air pollution and health (World Bank 2002). This book synthesizes learning and insights from various programs implementation across different socio-economic and geographic regions of the country. The critical issues related to dissemination of improves cook-stoves discussed in the book will find wide application not only in India but in other developing countries as well. It is imperative that we take forward the initiatives undertaken in the past to provide energy-efficient option for meeting the cooking needs of rural communities, yet underserved by modern energy options.